CNT@MnO2 Hybrid as Cathode Catalysts Toward Long‐Life Lithium Oxygen Batteries. Issue 21 (21st December 2016) - Wang, Fan; Wen, Zhaoyin; Wu, Xiangwei
Abstract: Rechargeable lithium‐oxygen (Li–O2 ) battery has attracted enormous research attention due to its remarkably high theoretical energy capacity. However, due to the sluggish oxygen reduction and oxygen evolution reaction (ORR and OER) kinetics and incidental side reactions in Li–O2 battery, cycle life is much shorter than that of lithium ion battery. Here, in‐situ growth of branched MnO2 nanosheets on carbon nanotubes (CNTs) were generated and applied as cathode catalyst in Li–O2 battery. The MnO2 with the morphology of petal‐like nanosheets were homogeneously coated outside the CNTs to form core‐shell nanowires. This structure can effectively prevent direct contact between the CNTs and Li2 O2, thus avoiding or reducing the decomposition of CNTs and the formation of Li2 CO3 during charge process, which can also improve the conductivity of the cathode and increase the cycling performance. As a promising cathode catalyst in Li–O2 batteries, the branched CNT@MnO2 nanocomposite cathode exhibits a stable deep discharge and charge cycling performance over 50 cycles, and more than 200 cycles with a fixed capacity of 500 mAh g –1 at a current density of 200 mA g –1 . Abstract : Coaxial structure: The MnO2 layer can effectively prevent direct contact between the CNTs and the discharge product decreasing the decomposition reaction of CNTs and prevent or reduce the formation of Li2 CO3 . Simultaneously the CNTs can improve the electronic conductivity of the air cathode. Thereby the overpotential could be reduced, rate and cycling performance be improved.